Mobile Gaming in Asia : Politics, Culture and Emerging Technologies - Jin, Dal Yong (Mobile Communication in Asia: Local Insights, Global Implications,, 2017)
This book analyzes mobile gaming in the Asian context and looks into a hitherto neglected focus of inquiry - a localized mobile landscape, with particular reference to young Asians' engagement with mobile gaming. This edition focuses not only on the remarkable success of local mobile games, but also on the significance of social milieu in the development of Asian mobile technologies and gaming culture. It analyzes the growth of the current mobile technologies and mobile gaming not as separate but as continuous developments in tandem with the digital economy. It is of interest to both academics and a broader readership from the business, government, and information technology sectors.